Comparative study of modeling, drying kinetics and specific energy consumption of desiccated coconut during convective and infrared drying - S., Yahya; A., Mohd Shamsul; A.G., Nur Hamizah; M.N., Mohd Zuhair (Rynnye Lyan Resources, 2024)
White coconut shreds were dried in this study utilizing convective (CD) and infrared (IR) drying methods to produce desiccated coconuts. The drying duration, drying rate, effective moisture diffusivity, activation energy, and specific energy consumption of desiccated coconuts were examined and compared between convective and infrared drying. The experiments were carried out at three level of air temperatures (50, 60 and 70°C) for convective drying and the same heating temperature was used for infrared drying. Air velocity of (1.5, 2.3 and 3.0 m/s) was supplied at every temperature for both drying methods. In order to determine the ideal model for desiccated coconuts, six mathematical models were fitted to both drying techniques with Page model providing a better fit than other models in all drying parameter ranges. Experimental drying curves displayed only a falling drying rate period. The experimental findings demonstrated that drying temperature, air velocity, and drying techniques had a substantial impact on drying kinetics. The highest effective moisture diffusivity value of desiccated coconuts was 1.66 x 10-9 m2 /s at (70°C and 3.0 m/s) and 2.79 x 10-9 m2 /s at (70°C and 1.5 m/s) from convective and infrared drying respectively. For convective and infrared drying, respectively, the specific energy consumption varied from 64.80 to 112.54 kWh/kg and 18.68 to 37.72 kWh/kg. The drying time between convective and infrared drying was inversely influenced by higher air velocity at same temperature. Air velocity had a substantial effect during infrared drying whereby the activation energy of 9.42 kJ/mol was the lowest at 2.3 m/s. Infrared drying proved to have better synergistic effect by providing higher drying rate and effective moisture diffusivity with the shortest drying time when compared to convective drying.